Active impulsive disturbance rejection and oscillation control of robot manipulator, using nonclassical rod models and proportional integral derivative controller. (December 2021) - Babaei, Alireza
Micro-electro-mechanical-systems scale robots are prone to impulsive disturbances during operation. Such disturbance leads to adverse oscillations of the robot manipulator. So, it is essential to mitigate and control such unwanted oscillations. On the other hand, to capture size dependencies of such robot elements, it is required to adopt nonclassical models. To address these cases, robot manipulator is modeled as a mechanical rod, comprehensive rod models are utilized, proportional integral derivative (PID) controller is designed, and the time-domain response of the system is simulated in MATLAB. Results show that adopting proper gain values of the PID controller leads to total rejection of the pulsive disturbances. However, findings conceal the importance of the nonclassical rod model such that strain gradient (SG) model shows less oscillatory amplitude than the classical theory (CT) model. While considering the nonlocal model effects (NL), such undesired vibrations are bigger than CT model. In other words, meanwhile, a simple PID controller can reject the disturbance for SG models; a stronger controller should be adopted to reject such pulsive disturbances with NL models. Eventually, it is valuable to note that to suppress unwanted oscillations in small-sized robots, PID closed-loop feedback controller is a decent choice because of the simplicity and less costs. Application of successful control design alongside the proper nonclassical theory leads to neutralizing the disturbances and increases the robot manipulator precision.